The Case Against User Interface Consistency - Grudin, Jonathan (Communications of the ACM, 1989)
Designers striving for user interface consistency can resemble Supreme Court justices trying to define pornqgraphy: each of us feels we know it when we see it, but people often disagree and a precise definition remains elusive. A close examination suggests that consistency is an unreliable guide and that designers would often do better to focus on users’ work environments.